2018
DOI: 10.1038/s41440-018-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 receptor cleavage in hypertension

Abstract: Increased protease activity causes receptor dysfunction due to extracellular cleavage of different membrane receptors in hypertension. The vasodilatory effects of insulin-like growth factor-1 (IGF-1) are decreased in hypertension. Therefore, in the present study the association of an enhanced protease activity and IGF-1 receptor cleavage was investigated using the spontaneously hypertensive rats (SHRs) and their normotensive Wistar Kyoto (WKY) controls (n = 4). Matrix metalloproteinase (MMP) activities were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Surprisingly, there have been few, if any, studies into the fate of these TIMP:MMP/ADAM12 complexes or whether combinations of these impart modulatory effects on TIMP2 function. To add further complexity to the system, many of TIMP2’s molecular targets can be proteolytically cleaved by metalloproteinase activity 6264 . We focused our in-depth analyses on breast and lung tumors, since we have found that TIMP2 can deliver therapeutic effects in murine models of these cancers and that they formed the nucleus of our identified study cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, there have been few, if any, studies into the fate of these TIMP:MMP/ADAM12 complexes or whether combinations of these impart modulatory effects on TIMP2 function. To add further complexity to the system, many of TIMP2’s molecular targets can be proteolytically cleaved by metalloproteinase activity 6264 . We focused our in-depth analyses on breast and lung tumors, since we have found that TIMP2 can deliver therapeutic effects in murine models of these cancers and that they formed the nucleus of our identified study cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage of its insulin receptors leads to the insulin resistance in the SHR . The ectodomain of the insulin‐like growth factor‐1 is clipped in the SHR . Endothelial apoptosis and the resulting capillary rarefaction in the SHR are due to the degradation of the VEGFR2, and the deficient leukocyte adhesion in the SHR is due to cleavage of membrane adhesion molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these, most significant results for PP in our study (4 out of 5 DMRs) were related to average levels during early pregnancy. Regions specific to PP included TRH, a gene implicated in the reduction of blood pressure in rats [75], and IGF1R a growth factor receptor which also participates in the regulation of blood pressure [76]. The two other DMRs were common with SBP: overlapping RNF141 and C6orf138 (PTCHD4), a gene found to be sensitive to transmitted adaptation to stress and associated with chronic obstructive pulmonary disease (COPD) [77,78].…”
Section: Discussionmentioning
confidence: 99%